Penjatuhan Sanksi Korupsi dan Pertanggungjawaban Tindak Pidana Korporasi Dalam Tindak Pidana Korupsi - Hasbullah, Ghufron (Sekolah Tinggi Agama Islam Taruna Surabaya, 2023)
Currently, corporations have a very important role for society, both positive and negative sides. The negative side of the large role of corporations is committing acts of corruption. In many cases of corruption, corporations are often caught and punished. The same thing happened to Decision No. 3/Pid.Sus-TPK/2018/PT.DKI which dropped the Main Director as the party responsible for corrupt behavior by corporations. The main focus of this research lies in criminal liability and the imposition of sanctions given to corporations. To make it easier to analyze the decision, researchers used normative legal research methods with a conceptual approach and statutory regulations. Based on the research results, it can be concluded that corporate criminal liability applied to Indonesian laws and regulations is mixed. On this basis, the judge imposed a sanction on the director of the corporation with imprisonment. In addition, the judge also imposed fines on corporations.